Urban Green Space as a Reservoir of Predatory Syrphids (Diptera, Syrphidae) for Aphid Control in Cities - Elżbieta Wojciechowicz-Żytko; Maja Dobińska-Graczyk (Agronomy)
The occurrence of predatory Syrphidae (hoverflies) in green areas of cities and their role as biological control agents is determined in this work. During the study, 751 adults belonging to 21 species were captured in Moericke’s traps and with sweep nets, and 286 larvae from 10 species were reared from aphid colonies. In both cases, the dominants were Episyrphus balteatus (Deg.) Sphaerophoria scripta (L.), and Syrphus vitripennis Meig. (L.) It can be assumed that hoverflies were attracted by flowering plants and then developed in aphid colonies on trees, shrubs, and herbaceous plants, reducing the aphid population. The largest number of hoverflies was caught in the plant-rich and well-developed Wolski Forest, whose conditions were beneficial for their reproduction and survival. Studies on the voracity of hoverflies have shown that the larvae of dominant species ate from 243 to 498 individuals of Aphis fabae Scop. and from 272 to 468 specimens of Myzus cerasi (Fabr.); the efficiency depended on the syrphid and aphid species as well as the instar stage of the syrphid larva. The results indicate that urban green spaces are vital refugia for insect biodiversity and could be a reservoir of beneficial insects.